PERAN SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS PELAPORAN KEUANGAN DINAS KESEHATAN KABUPATEN BUTON SELATAN - Laode Muhammad Hasrul Adan; La Ode Abdul Wahidin (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2024)
The need for accountability in regional financial management has driven governments to improve the quality of financial reporting. This study aims to analyze the role of accounting information systems in the quality of financial reports at the Health Office of South Buton Regency. This research employs a qualitative descriptive method, with data collected through observation and interviews with financial officials/staff directly involved in reporting. The results indicate that the implementation of the Regional Government Information System (SIPD) meets the characteristics of a good accounting information system—namely relevance, accuracy, timeliness, and completeness. Furthermore, the financial reports produced are considered relevant, reliable, comparable, and understandable. These findings imply that SIPD plays a significant role in enhancing the quality of financial reporting, thereby supporting decision-making and promoting accountable and transparent governance.